Identifying Genomic Alterations in Small Cell Lung Cancer Using the Liquid Biopsy of Bronchial Washing Fluid - Zhai, Jinfang; Han, Songyan; Guo, Qinxiang; Shan, Binbin; Wang, Jing; Guo, Yanrong; Tong, Guoping; Zhao, Chang; Li, Yuan; Han, Qiao; An, Xiaoqin; Yue, Ruiqing; et al. (Frontiers in Oncology, 2021)
Objective With the rapid development of cancer genomics and immunomics, some new treatments of small cell lung cancer (SCLC) is emerging. However, there are limitations to the clinical use of tumor tissue. Our study aimed to evaluate the potential use of bronchial washing fluid (BWF) in the liquid biopsy of SCLC. Methods Twenty-one extensive SCLC (ES-SCLC) patients were enrolled in this study. For all patients, four sample types, BWF supernatant (BWFs), BWF precipitate (BWFp), plasma and tumor tissue, were collected before receiving chemotherapy, and one type, plasma, was collected after chemotherapy. All samples were conducted to NGS using the 1021-gene panel. The concordance rates of genomic profiling using NGS in the four types samples were evaluated. Multiple clinical information was analyzed for correlation. Results We successfully tested 20 BWFs samples, 21 BWFp samples, 21 tumor tissue samples, 20 pre-treatment plasma and 13 post-treatment plasma of these 21 patients. The detectability of somatic mutations was 100% for BWFs, BWFp, tumor tissues and post-treatment plasma, and only one pre-treatment plasma was absent with any mutation. Matched tumor tissue, BWFs, BWFp and pre-treatment plasma samples were subsistent for 19 patients. For these patients, 204 genomic alterations were identified in tissue samples, while 189 (92.6%), 175 (85.5%) and 163 (79.9%) alterations were detected in the matched BWFs, BWFp and pre-treatment plasma, respectively. Moreover, we found that the three tumor markers associated with SCLC have a lower sensitivity than genomic alterations. Endocrine resistance pathway was found enriched in hyponatremia patients which may be related to the hyponatremia. The TMBs of BWFs, BWFp and pre-treatment plasma samples all had strong correlation with that of tissue samples. Both the VAF and the MVAF of mutations in post-treatment plasma were less than those in pre-treatment plasma, which was in accordance with the evaluation of curative effect. Conclusions For ES-SCLC patients, the liquid biopsy of BWF showed highly potential advantage to identify DNA alterations, which suggested that genomic analysis of BWF liquid biopsy may have clinical value as a supplement for tissue and blood detection. Through the restrict validation, it can be widely used in routine clinical practice.